Beyond Pepper v. Hart: The legislative reform of statutory interpretation in Singapore - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 1994)
One of the major controversies in the area of statutory interpretation has centred on the use of parliamentary materials as extrinsic aids by courts in interpreting legislation. The English courts long prohibited any reference to parliamentary materials.' Legislation was passed in Australia in the 1980s to allow liberal reference to parliamentary materials in the courts.2 More recently, a seminal decision of the House of Lords in 1992 in Pepper (Inspector of Taxes) v. Hart' introduced significant flexibility into the hitherto rigid proscription followed in the English courts, although it did not go as far as the legislative reforms in Australia. Pepper v. Hart was immediately applied by courts in Singapore in two cases.4 Shortly thereafter, in early 1993, the Singapore Parliament passed legislation5 modelled on that in Australia. Like the legislation in Australia, it also directs courts to give statutory provisions an interpretation which would promote the object or purpose underlying the statute. This article will examine these developments and assess their likely impact on the practice of the courts in Singapore.